Design, Synthesis, and Herbicidal Activity of Novel 5-Acylbarbituric Acid Derivatives Containing a Pyrimidinedione Moiety - Ke Chen; Shumin Wang; Shuyue Fu; Wei Gao; Junehyun Kim; Phumbum Park; Rui Liu; Kang Lei (Agronomy)
In continuation of our efforts to identify novel herbicide lead compounds with enhanced activity, a series of eighteen 5-acylbarbituric acid derivatives containing a pyrimidinedione moiety were designed and synthesized. Their herbicidal activities were subsequently evaluated in the greenhouse. Bioassay results demonstrated that most of the newly synthesized compounds exhibited significant herbicidal efficacy at a dosage of 150 g ha−1, with compounds BA-I-2, BA-II-2, BA-III-2, and BA-III-5 achieving complete inhibition of the tested weeds. Further investigation into the herbicidal spectrum revealed that compounds BA-II-2 and BA-III-2 displayed excellent herbicidal activity against 14 and 13 out of 16 tested weed species, respectively, with inhibition rates exceeding 80% at dosages as low as 18.8 g ha−1. More promisingly, compound BA-III-2 was found to be safe for Triticum aestivum at a dosage of 37.5 g ha−1. Molecular mode of action studies, including phenotypic observations, membrane permeability evaluations, and molecular docking, suggested that BA-III-2 may function as a protoporphyrinogen IX oxidase (PPO) inhibitor. The present work indicates that BA-III-2 holds potential as a PPO-inhibiting herbicide for effective weed control in wheat fields and is expected to provide important theoretical foundations for the development of novel and highly efficient herbicides.